Preliminary Exploration of Bacteriophages Targeting Mycobacterium smegmatis from Hospital Wastewater in Bekasi, Indonesia - Rina Hidayati Pratiwi; Nadiva Viraniswah; Mashudi Alamsyah; Saad Aboualkasem (Poltekkes Kemenkes Surabaya, 2026)
Tuberculosis (TB) remains a major global health problem, exacerbated by the emergence of multidrug-resistant strains. Bacteriophages, particularly lytic phages, are gaining increasing attention as alternative antimicrobial agents due to their specificity and low resistance potential. This is a pilot study aimed at isolating lytic bacteriophages from hospital and domestic wastewater that exhibit activity against Mycobacterium smegmatis (M.sm) as a model organism for Mycobacterium tuberculosis (M.tb). Wastewater samples were collected from five locations and tested for lytic activity using a spot test on M.sm. The results confirmed the presence of phages in four of the five samples, as evidenced by plaque formation with varying morphology. Plaques from samples coded ABR and ABM were mostly clear and large, indicating strong lytic activity, while samples coded IS and VB showed more diverse plaque shapes, including turbid and small plaques. This difference reflects the influence of environmental origin on phage diversity. The highest plaque diversity was observed in samples with high organic content and microbial richness, supporting the hypothesis that phage-host interactions are shaped by environmental factors.